Upaya Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PKn Materi Nilai Pancasila di Kelas VIII C SMPN 2 Manyar melalui Model Pembelajaran Kooperatif Tipe CIRC - S, Siami (JURNAL WAHANA PENDIDIKAN DASAR, 2016)
The finding of the initial study and conversation with student of SMPN VIII.C Class 2 Manyar Gresik in mid-September in the school year 2013/2014, there was information that the students are still many who have difficulty in understanding the subject of Civic Education, at the outlining material contained values in Pancasila, so that the problem in research that can be disclosed are: 1) is the CIRC type of cooperative learning model can improve student learning outcomes on the subjects of Civic Education in the classroom VIII.C SMPN 2 Manyar Gresik? 2) The extent to which the efforts of the CIRC type of cooperative learning model can improve student learning outcomes on the subjects of Civic Education in the classroom VIII.C SMPN 2 Manyar Gresik? Researcher are VIII C Civic teacher at SMPN 2 Gresik, until now. Object in a class action research (PTK) is the action taken on the implementation of learning activities in the  classroom SMPN 2 Manyar Gresik VIII.C as many as 30 students in the first semester of school year2013-2014 , research was conducted for 3 (three) months, namely began the third week of September 2013 until the first week of Desember 2013, through three cycles. In general, the study cycles through the step of planning, implementation, observation, and reflection activities. In particular, it can be conclude as follows: 1) The mean score is experiencing an increase students understanding od cycle I to III, the first cyle of 72.7 in the second cycle of 75.62, while the third cycle of 87.5. Similarly, the completion of the study in the first cycle 45.83% in the second cycles to 62.5%, while in the third cycles to 100% 2) In the method of learning with cooperative learning model CIRC teacher must also consider the importance of classroom management. It is for smooth process of learning. Because even in the own learning teaching mehods were good however if less well in managing.